2012
DOI: 10.2527/jas.2011-4684
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in the arcuate nucleus of heifers is affected by controlled intake of high- and low-concentrate diets1

Abstract: It was hypothesized that a high-concentrate diet fed during early calfhood alters the expression of genes within the arcuate nucleus that subserve reproductive competence. Beef heifers (n = 12) were weaned at approximately 3 mo of age, and after acclimation, were allocated randomly to 1 of 2 nutritional groups: 1) High Concentrate/High Gain (HC/HG), a high concentrate diet fed to promote a gain of 0.91 kg/d; or 2) High Forage/Low Gain (HF/LG), a forage-based diet fed to promote a gain of 0.45 kg/d. Experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 73 publications
2
45
0
11
Order By: Relevance
“…Previous studies have revealed that transcriptional and morphological alterations within the hypothalamic NPY network are involved in the sexual maturation of heifers (Alves et al 2011, Allen et al 2012. Results from the current study provide further evidence that the .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have revealed that transcriptional and morphological alterations within the hypothalamic NPY network are involved in the sexual maturation of heifers (Alves et al 2011, Allen et al 2012. Results from the current study provide further evidence that the .…”
Section: Discussionsupporting
confidence: 79%
“…Using similar nutritional models, it has been demonstrated previously that the expression of NPY mRNA in the ARC was decreased in prepubertal heifers that gained BW at a relatively high rate (Allen et al 2012). Furthermore, the proportion of GnRH neurons in close proximity to NPY fibers in the preoptic area and mediobasal hypothalamus is reduced in heifers with increased BW gain (Alves et al 2011).…”
Section: Discussionmentioning
confidence: 79%
“…On the contrary, feeding a highconcentrate diet to beef heifers decreased the expression of hypothalamic NPY and AgRP in comparison to a high-forage diet [60]. Thus, dietary constitutes and energy balance affect the transcription of central signals regulating feed intake and energy expenditure in ruminants.…”
Section: Effect Of Lipids On Hypothalamic Signals Regulating Feed Intakementioning
confidence: 95%
“…Many experiments have been conducted to quantify the requirements of energy, protein, and minerals of pregnant animals (Bell et al, 2005;Ferrell, 1991;Ferrell et al, 1976) and the impact of early calfhood nutrition on their reproductive development (Allen et al, 2012;Alves et al, 2015;Amstalden et al, 2014;Cardoso et al, 2014a;Cardoso et al, 2014b). However, not until recently have scientists inquired about controlling the type and quality of the nutrition during fetus development and its long-lasting impacts on the growth and development of the newborn through adulthood: the fetal programming theory.…”
Section: Early Nutritional Fetal Programmingmentioning
confidence: 99%